Penggunaan Bahasa Iklan di Media Sosial Aplikasi Tiktok: Analisis Pragmatik pada Iklan Pruduk Kecantikan Skintific - Malikha, Usrin (Universitas Al-Qolam Malang, 2024)
This study examines the use of language in beauty product advertisements on TikTok, specifically focusing on the Skintific brand. The research aims to analyze how the language in these advertisements affects the audience's reception of the message. Utilizing a pragmatic approach, the study investigates the persuasive language techniques employed in TikTok advertisements, such as the use of imperative sentences, persuasive claims, and product comparisons. Through a qualitative analysis of selected Skintific ads, this research identifies key linguistic strategies that enhance product appeal and motivate audience behavior, particularly in relation to purchase decisions. The findings reveal that the use of persuasive language, such as terms highlighting product effectiveness and safety, along with calls to action like